Estimating Skeletal Maturity by Segmented Linear Modeling of Key AP Knee Radiographic Parameters. Issue 3 (March 2022) - Yuan, Joshua T.; Furdock, Ryan J.; Benedick, Alex; Liu, Raymond W.
Abstract : Background: The recently described Modified Fels knee system allows for accurate skeletal maturity estimation using a single anteroposterior knee radiograph but requires evaluation of 7 parameters. A faster method may have clinical utility in the outpatient setting. Methods: Seven anteroposterior knee radiographic parameters associated with 90% of the final height (an enhanced skeletal maturity standard compared with peak height velocity) were analyzed in 78 children. Segmented linear regression and generalized estimating equation analyses were used to identify the subsets of parameters most important for accurate skeletal maturity estimation for different patient demographics and parameter scores. This process produced abbreviated skeletal maturity systems, which include fewer parameters and are quicker to use. The accuracy of the resulting abbreviated skeletal maturity systems was evaluated and compared with the full 7-parameter Modified Fels knee system and with the Greulich and Pyle (GP) left-hand bone age. Results: A total of 326 left knee radiographs from 41 girls (range, 7 to 15 y) and 37 boys (range, 9 to 17 y) were included. Models generated by segmented regression and generalized estimating equation analysis required fewer parameters (range, 1 to 5 parameters) than the full Modified Fels knee system (7 parameters). Skeletal age estimates produced by segmented regression models were more accurate than GP ( P <0.05) and not significantly different from the full Modified Fels system ( P >0.05). The percentage of outlier estimations (estimations >1 y off from actual skeletal age) made by segmented regression models was not significantly different from GP ( P >0.05) or the Modified Fels knee system ( P >0.05). Conclusion: An abbreviated version of the Modified Fels knee system estimates skeletal maturity more accurately than the GP system with just 2 to 3 radiographic knee parameters. Clinical Relevance: The abbreviated Modified Fels knee system may allow for rapid skeletal age estimation (~30 s) appropriate for routine outpatient practice.